Is a definitive trial of prehospital continuous positive airway pressure versus standard oxygen therapy for acute respiratory failure indicated? The ACUTE pilot randomised controlled trial. Issue 7 (23rd July 2020) - Fuller, Gordon; Keating, Sam; Goodacre, Steve; Herbert, Esther; Perkins, Gavin; Rosser, Andy; Gunson, Imogen; Miller, Josh; Ward, Matthew; Bradburn, Mike; Thokala, Praveen; Harris, Tim; et al.
Abstract : Objectives: To determine the feasibility of a large-scale definitive multicentre trial of prehospital continuous positive airway pressure (CPAP) in acute respiratory failure. Design: A single-centre, open-label, individual patient randomised, controlled, external pilot trial. Setting: A single UK Ambulance Service, between August 2017 and July 2018. Participants: Adults with respiratory distress and peripheral oxygen saturations below British Thoracic Society target levels despite controlled oxygen treatment. Interventions: Patients were randomised to prehospital CPAP (O-Two system) versus standard oxygen therapy in a 1:1 ratio using simple randomisation. Primary and secondary outcome measures: Feasibility outcomes comprised recruitment rate, adherence to allocated treatment, retention and data completeness. The primary clinical outcome was 30-day mortality. Results: 77 patients were enrolled (target 120), including 7 cases with a diagnosis where CPAP could be ineffective or harmful. CPAP was fully delivered in 74% (target 75%). There were no major protocol violations. Full data were available for all key outcomes (targets ≥90%). Overall 30-day mortality was 27.3%. Of these deceased patients, 14/21 (68%) either did not have a respiratory condition or had ceiling of treatment decisions implemented excluding hospital non-invasive ventilation and critical care. Conclusions: Recruitment rate was below target and feasibility was not demonstrated. Limited compliance with CPAP, and difficulty in identifying patients who could benefit from CPAP, indicate that prehospital CPAP is unlikely to materially reduce mortality. A definitive effectiveness trial of CPAP is therefore not recommended. Trial registration number: ISRCTN12048261; Post-results .